Be careful and stay safe - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit Pub., 2007)
Teaches young children basic skills for staying safe in daily situations and preparing for emergencies, and provides an activity guide for adults.
2.8
K-3
K-3
Keywords: Accidents -- Prevention -- Juvenile literature; Children's accidents -- Prevention -- Juvenile literature; Safety education -- Juvenile literature; Safety; Accidents -- Prevention; Safety education